An analysis of dominant discourse in Grade 8 English Home Language textbooks - Cahl, Gregory Elkan (School of Education, 2017)
Post-Apartheid South Africa has heralded a period of intense curriculum reform, explicitly aimed at fostering social transformation and a shift from the uncritical rote-learning which dominated Apartheid-era schooling. There have been three major curriculum shifts since 1994 and each change has required the production of new textbooks for every single school subject, usually within highly limited time-frames. This study focuses on textbooks produced for the most recent iteration of the Language curriculum, that is, the Curriculum Assessment Policy Statement, commonly known as CAPS. The study draws on poststructuralist theory on discourse, in particular Critical Discourse Analysis (CDA), to engage in close, critical analysis of the dominant discourses in two grade 8 English home language learner textbooks. The textbooks are examined in terms of how social issues are depicted; the notions of English education; the extent to which they promote a critical approach to language and literacy learning as outlined in the curriculum and the ways in which learners are constructed as subject. The analysis of different levels of discourse evident in the texts and text-based tasks demonstrates that the orientations to reading that are offered are focussed largely on the surface meaning of the texts. While social issues related to contemporary South African and global topics are evident in the choice of content, the texts often perpetuate fairly conservative ideologies, either through their content, the exercises that follow or through the silences implicit in the selection of excerpts. Many of the text-based exercises are decontextualized, cognitively undemanding and learners are often steered towards particular answers, leaving very limited space for critical engagement. The thesis ends with a consideration of the implications of this analysis for teaching and learning.